Updated insights into predictive biomarkers for response to cardiac resynchronization therapy - A literature review - Pal Krisztina; Cotoi Ionela M.; Vlad Georgiana G.; Lupu Silvia (Romanian Journal of Laboratory Medicine, 2023)
Cardiac resynchronization therapy (CRT) was shown to greatly improve outcomes in specific patients with heart failure, low ejection fraction and wide QRS complex; however post-therapeutic response is heterogeneous and currently difficult to predict. There is an increasing interest in identifying humoral biomarkers which could help stratify prognosis, and better identify responders. The aim of this review was to provide an overview of recent data regarding the predictive value of biomarkers for evaluating response to CRT. A definitive conclusion cannot currently be drawn due to disparate results, varying methodologies, relatively small-scale studies and lack of consensus in defining CRT response. More extensive comparable research is paramount to facilitate progress in this field.